2021
DOI: 10.1021/acs.analchem.1c01235
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Cocatalyst on a Photoanode in Water Splitting: A Study of Scanning Electrochemical Microscopy

Abstract: With a proper band gap of ∼2.4 eV for solar light absorption and suitable valence band edge position for oxygen evolution, scheelite-monoclinic bismuth vanadate (BiVO 4 ) has become one of the most attractive photocatalysts for efficient visible-light-driven photoelectrochemical (PEC) water splitting. Several studies have indicated that surface modification of BiVO 4 with a cocatalyst such as NiFe layered double hydroxide (LDH) can significantly increase the PEC water splitting performance of the catalyst. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…17 It is worth noting that the loading of highly active oxygen evolution co-catalysts has been proven to be a promising strategy for building an efficient PEC photoanode. 18 A number of oxygen evolution co-catalysts such as CoPi, 19 CoBi, 20 MCo 2 O 4 (M = Mn, Zn), 21 CoOOH, 22 and FeOOH/NiOOH 23,24 have been researched to decrease the onset potential and accelerate the oxygen evolution reaction (OER) at the electrode/electrolyte interface. In the Co based co-catalyst studies, cobalt phosphate (CoPi) has been widely used due to the low cost, convenient preparation and excellent OER activity in PEC water oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…17 It is worth noting that the loading of highly active oxygen evolution co-catalysts has been proven to be a promising strategy for building an efficient PEC photoanode. 18 A number of oxygen evolution co-catalysts such as CoPi, 19 CoBi, 20 MCo 2 O 4 (M = Mn, Zn), 21 CoOOH, 22 and FeOOH/NiOOH 23,24 have been researched to decrease the onset potential and accelerate the oxygen evolution reaction (OER) at the electrode/electrolyte interface. In the Co based co-catalyst studies, cobalt phosphate (CoPi) has been widely used due to the low cost, convenient preparation and excellent OER activity in PEC water oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, compared to dark conditions, more warm color is clearly seen, revealing that holes from BWO can be in situ -captured and take part in the oxidation reaction of probe molecules, as confirmed by the positive feedback curves. Based on the simplest kinetic model, the fitting kinetic constant ( K eff ) of relevant photoanodes can be calculated. As shown in Figure c and Table , the K eff increases in the following order: BWO < BWO/BS < BWO/BS/Au < BWO/Au/BS.…”
Section: Resultsmentioning
confidence: 99%
“…Tan et al studied monolayer chemical-vapor deposited graphene defects by the SECM feedback mode (Figure B), and the results showed that the reactivity of graphene defect sites to electrochemical reactions was about one order of magnitude higher than that of more primitive graphene surfaces . Yu et al investigated the effect of NiFe layered double hydroxide (LDH) cocatalyst on BiVO 4 photoanode by SECM feedback mode (Figure C) . Studies on the photocatalyst and redox reaction of BiVO 4 /NiFe-LDH show that the rate constant of the photoluminescent hole ( k h+ 0 ) and electron ( k e– 0 ) is five times larger than that of BiVO 4 under illumination.…”
Section: Basic Information On Secmmentioning
confidence: 99%